Associations between rate of force development metrics and throwing velocity in elite team handball players: a short research report - Marques, M. C.; Saavedra, F. J.; Abrantes, C.; Aidar, F. J. (Journal of Human Kinetics, 2011)
Performance assessment has become an invaluable component of monitoring participant'fs development in distinct sports, yet limited and contradictory data are available in trained subjects. The purpose of this study was to examine the relationship between ball throwing velocity during a 3-step running throw in elite team handball players and selected measures of rate of force development like force, power, velocity, and bar displacement during a concentric only bench press exercise in elite male handball players. Fitteen elite senior male team handball players volunteered to participate. Each volunteer had power and bar velocity measured during a concentric only bench press test with 25, 35, and 45 kg as well as having one-repetition maximum strength determined. Ball throwing velocity was evaluated with a standard 3-step running throw using a radar gun. The results of this study indicated significant associations between ball velocity and time at maximum rate of force development (0, 66; p<0.05) and rate of force development at peak force (0,56; p<0.05) only with 25kg load. The current research indicated that ball velocity was only median associated with maximum rate of force development with light loads. A training regimen designed to improve ball-throwing velocity in elite male team handball players should emphasize bench press movement using light loads.